1978
DOI: 10.1007/bf00235811
|View full text |Cite
|
Sign up to set email alerts
|

Studies on RNA metabolism in the nerve cells of Hippocampus during training in rats

Abstract: Direct evidence is presented that training to change behavior initiates synthesis of specific species of mRNA in pyramidal nerve cells of CA3 of the hippocampus in rats. Reversal of handedness was used as goal-directed operant test and active controls. Newly synthesized poly(A) associated mRNA with S value of 25 and a stimulation of poly(A) lacking mRNA of 8--9 S and 16--17 S were found in the CA3 nerve cells of trained but not in active controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Most eukaryotic mRNAs and hnRNAs (heterogeneous nuclear RNA) contain sequences of polyadenylic acid about 200 nucleotides-long at the 3'-OH terminus (Edmonds and Caramela, 1969;Lim and Canellakis, 1970; Edmonds et al, 1971; Nakazato a n d E d m o n d s , 1972; DeLarco and Guroff, 1972; B a n k s a n d J o h n s o n , 1973; Hemminki, 1974;L i m et al, 1974;Mahony and Brown, 1975;Bondy et al, 1977;Cupello and Hyden, 1978). Poly(A)-containing RNA (poIy(A)+ RNA) can be selectively bound to oligo(dT)-cellulose; thus, the presence of such p o l y ( A ) sequences in most eukaryotic mRNA provides a method for its identification as well as a means for its isolation.…”
mentioning
confidence: 99%
“…Most eukaryotic mRNAs and hnRNAs (heterogeneous nuclear RNA) contain sequences of polyadenylic acid about 200 nucleotides-long at the 3'-OH terminus (Edmonds and Caramela, 1969;Lim and Canellakis, 1970; Edmonds et al, 1971; Nakazato a n d E d m o n d s , 1972; DeLarco and Guroff, 1972; B a n k s a n d J o h n s o n , 1973; Hemminki, 1974;L i m et al, 1974;Mahony and Brown, 1975;Bondy et al, 1977;Cupello and Hyden, 1978). Poly(A)-containing RNA (poIy(A)+ RNA) can be selectively bound to oligo(dT)-cellulose; thus, the presence of such p o l y ( A ) sequences in most eukaryotic mRNA provides a method for its identification as well as a means for its isolation.…”
mentioning
confidence: 99%
“…In addition to the task difficulty, the bimanual use in the present task might also elevate cognitive demand. It has been reported that rats show handedness, i.e., a preference to use the right forepaw [ 20 ], and that reversal of handedness activates the hippocampus [ 21 ]. The dependency of hippocampal theta oscillations on task difficulty is like that reported in FM theta [ 22 ].…”
Section: Introductionmentioning
confidence: 99%